Environmental effects on the UV upturn in local clusters of galaxies - Sadman S. Ali; Malcolm N. Bremer; Steven Phillipps; Roberto De Propris (OXFORD UNIV PRESS, 2022)
We explore the dependence of ultraviolet (UV) upturn colours in early-type cluster galaxies on the properties of their parent clusters (such as velocity dispersion and X-ray luminosity) and on the positions and kinematics of galaxies within them. We use a sample of 24 nearby clusters with highly complete spectroscopy and optical/infrared data to select a suitable sample of red-sequence galaxies, whose far-ultraviolet and NUV magnitudes we measure from archival GALEX data. Our results show that the UV upturn colour has no dependence on cluster properties and has the same range in all clusters. There is also no dependence on the projected position within clusters or on line-of-sight velocity. Therefore, our conclusion is that the UV upturn phenomenon is an intrinsic feature of cluster early-type galaxies, irrespective of their cluster environment.